Jazz Colors: Pigment Identification in the Gouaches Used by Henri Matisse - Ana Martins; Anne Catherine Prud’hom; Maroussia Duranton; Abed Haddad; Celine Daher; Anne Genachte-Le Bail; Tiffany Tang (Heritage, 2021)
Jazz, the illustrated book by Henri Matisse, is a testament to the vitality of the artist in the last decade of his career. The book consists of twenty illustrations reproduced in 370 copies using a stencil-based printing technique and the same Linel gouaches the artist had used for the original maquettes. This study reports on the comprehensive analysis carried out to identify the pigments in the gouaches used in Jazz by transmitted and reflectance infrared, Raman, SERS, and X-ray fluorescence spectroscopies, and describes the lightfastness of these gouaches as evaluated by microfaedometry. This study also highlights the necessity of a multi-analytical approach for comprehensive identification of artist materials and investigates the suitability of portable and non-invasive techniques. The results were consistent across the three copies investigated: a portfolio in the collection of the Museum of Modern Art in New York and two books in the collection of the Musée National d’Art Moderne in Paris. In total, 39 distinct colors were characterized, with the magenta, pinks, and blues being the most fugitive.